Kinetic Studies on the Selectivity of a Synthetic Thrombin-Inhibitor Using Synthetic Peptide Substrates - Huikata, A; Okamoto, S; Kikumoto, R; Tamao, Y (Thrombosis and Haemostasis, 1979)
The synthetic thrombin-inhibitor termed No. 205 (N-α-dansyl-L-arginine-4-ethyl-piperidine amide) found in our laboratories was studied kinetically using synthetic peptide substrates. The following results were obtained. 1. No. 205 inhibited thrombin competitively with bz-Phe-Val-Arg-pNA and the Ki value obtained was extremely small, 3.7 × 10-8 M. 2. No. 205 also inhibited trypsin competitively with bz-Phe-Val-Arg-pNA but the Ki value obtained was far larger than that for thrombin, 1.0 × 10-5 M. 3. No. 205 inhibited F. Xa, plasmin and urokinase only to a small extent when estimated using 2 × 10-4 M D-Val-Leu- Lys-pNA, bz-Ile-Glu-Gly-Arg-pNA and Glu-Gly-Arg-pNA, respectively. 4. No. 205 differed from APPA in its specific inhibitory spectrum for thrombin as compared to trypsin, plasmin and F. Xa. The above results indicate that No. 205 is an extremely potent and highly selective reversible thrombin-inhibitor.